Holocene eruptive history of Ksudach volcanic massif, South Kamchatka: evolution of a large magmatic chamber - Volynets O.N.; Ponomareva V.V.; Braitseva O.A.; Melekestsev I.V.; Chen Ch.H. (Journal of Volcanology and Geothermal Research, 1999)
The combination of geological, tephrochronological and geochemical studies is used to reconstruct the Holocene eruptive history of Ksudach volcanic massif, South Kamchatka and to trace the evolution of its magma. Ksudach is located in the frontal volcanic zone of Kamchatka. From Early Holocene till AD 240, the volcano had repetitive voluminous caldera-forming eruptions. Later they gave way to frequent moderate explosive–effusive eruptions that formed the Shtyubel' stratovolcano inside the nested calderas, and then to frequent larger explosive eruptions. Holocene eruptive products are low-K2O two pyroxene–plagioclase basaltic andesite to rhyodacite. Mineralogical, geochemical and isotopic data suggest that all the rock varieties originated as a result of fractionation of an initial mafic melt, with insignificant contamination and assimilation. Intensive mixing of the fractionating melts prior to, and during the course of the eruptions, is ubiquitous. The eruptions might have been triggered by repetitive injections of new mafic melt into the silicic chamber. Crystallization of the andesitic and rhyodacitic melts is estimated to have occurred at temperatures of 970–1010°C and 890–910°C, respectively, PH2O 1.5–2.0 kbar and fO2 close to the NNO buffer. According to the experimental data, such PH2O corresponds to 4.5%–5.5% of water in the melt, that is close to the content of water in the silicic hornblende-bearing magmas of the rear zone of the Kuril–Kamchatka arc. Hence, we suggest that the transition from pyroxene phenocryst associations of the frontal zone to the hornblende-bearing ones of the rear zone might be interpreted as reflecting higher temperatures of crystallization of the melts from the frontal zone rather than increasing water content in the rear zone magmas.